Frequency of causes of Pancytopenia based on bone Marrow Smear Results in patients 1 year to 12 years age - Fizzah Mehwish, Sidra Shafique, Beenish Fatima (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the frequency of causes of pancytopenia based on bone marrow smear examination in children aged 1 to 12 years. Design: Descriptive, cross sectional study. Place and duration of study: Hematology outpatients department, children hospital complex, Multan from June 2019 to December 2019. Patients and methods: All patients aged 1-15 years were included who presented with pancytopenia. Already diagnosed cases, cases who had received blood transfusion, cases with inherited or congenital pancytopenia were excluded. History, physical examination and hematological profile were recorded at presentation which included Hb, white blood cells count, platelets count, peripheral morpholgy and bone marrow smear. Results: During research, 139 patients with pancytopenia on the basis of peripheral blood morphology were added. Causes of pancytopenia based on bone marrow smear results were identified in 118 (84.8%) cases while in 21 cases no cause was identified. Among those, most frequent was aplastic anemia (43.8%), megaloblastic anemia (33.8%), acute lymphoblastic leukemia (5%) and myelodysplastic syndrome. Common clinical findings were pallor, fever, generalized weakness and bleeding manifestations. Conclusion: Pancytopenia is a usual findings in patients presenting to hematology department. Though aplastic anemia is frequently found, megaloblastic anemia can be treated easily. Acute lymphoblastic leukemia is rate.